From youth to youth: engineering undergraduates attracting school students to engineering education - Othman, Hussain; M. Salleh, Berhannuddin; Sulaiman, Abdullah; Selamat, Asri (Taylor and Francis, 2009)
Malaysia is moving forward to increase the number of profesional engineers in five years ahead. Some four new technical universities have been established since 2000. Unfortunately, the interest to study engineering among young generation does not increase as much as anticipated by the government. Most of the students were reluctant to choose engineering as their first choice and yet some were forced by their parents to choose the engineering programs. Having established as an engineering university, University Tun Hussein Onn Malaysia has identified some approaches to improve the situation and one of which involves its undergraduates as coordinators. As a part of university’s generic skills assessment program, a group of 70 engineering undergraduates had organized a motivational project called Student’s Guided Motivational Program to 395 school students. A study was conducted on the learning motivation and the interest of school students towards their future career. Pre-survey showed that only 8.4% of the students were interested to become engineers whereas the rest opted for other careers. However, post-survey conducted at the end of the program had surprisingly recorded the increasing percentage to 67.8% students opted for engineer as their future career. Thus, this proved the success of the program in enhancing the interest of school students towards engineering education.